Metabolic Engineering of the Phenylpropanoid Pathway Enhances the Antioxidant Capacity of Saussurea involucrata - Qiu, Jian; Gao, Fenghua; Shen, Guoan; Li, Chonghui; Han, Xiaoyan; Zhao, Qiao; Zhao, Dexiu; Hua, Xuejun; Pang, Yongzhen (PLOS ONE, 2013)
The rare wild species of snow lotus Saussurea involucrata is a commonly used medicinal herb with great pharmacological value for human health, resulting from its uniquely high level of phenylpropanoid compound production. To gain information on the phenylpropanid biosynthetic pathway genes in this critically important medicinal plant, global transcriptome sequencing was performed. It revealed that the phenylpropanoid pathway genes were well represented in S. involucrata. In addition, we introduced two key phenylpropanoid pathway inducing transcription factors (PAP1 and Lc) into this medicinal plant. Transgenic S. involucrata co-expressing PAP1 and Lc exhibited purple pigments due to a massive accumulation of anthocyanins. The over-expression of PAP1 and Lc largely activated most of the phenylpropanoid pathway genes, and increased accumulation of several phenylpropanoid compounds significantly, including chlorogenic acid, syringin, cyanrine and rutin. Both ABTS (2,2′-azinobis-3-ethylbenzotiazo-line-6-sulfonic acid) and FRAP (ferric reducing anti-oxidant power) assays revealed that the antioxidant capacity of transgenic S. involucrata lines was greatly enhanced over controls. In addition to providing a deeper understanding of the molecular basis of phenylpropanoid metabolism, our results potentially enable an alternation of bioactive compound production in S. involucrata through metabolic engineering.